Antimicrobial Activity of Saponins Isolated from Achyranthus aspara against Staphylococcus aureus - Sharma, Sunita; Shrivastava, P.N.; Saxena, R.C. (Asian Journal of Chemistry, 2010)
Achyranthus aspara Linn. (family Amaranthaceae) alcoholic extract showed the presence of the triterpenoid saponin with dose dependent inhibitory activity against Staphylococcus aureus, a bacteria causing skin disease in human beings. Minimum inhibitory concentration was found to be highest (0.15 mg) for purified fraction-3. The identification of the compound on spectral analysis gave a triterpenoidal saponin purified fraction.